# solve 2x-7(x-5)=0

*print*Print*list*Cite

### 6 Answers

2x-7(x-5)=0 Multiply -7 by what's in the parenthesis

2x-7x+35=0 Add like terms 2x-7x= -5x

-5x+35=0

-5x-35=0-35 Subtract 35 on both sides of the equal sign

-5x =-35

-5x/-5=-35/-5 Divide -5 on both sides of the equal sign

x=7 answer

2x-7(x-5)=0

In order to solve this you need to isolate x

2x - 7x + 35 = 0 (remove parenthesis by multiplying both by 7)

2x - 7x + 35 - 35 = -35 (subtract 35 from both sides)

2x - 7x = -35

-5x = -35

-5x/-5 = -35/-5 (divide both sides by -5)

**x = 7 Answer.**

2x-7(x-5)=0

2x-7x+35=0

-5x=-35

x=7

2x - 7 ( x - 5 ) = 0

First distribute the -7

2x - 7x + 35 = 0 now combine the like terms ( 2x and -7x )

By combining the like terms, you should get

-5x + 35 = 0 subtract 35 on both sides

By subtracting, you should get

-5x = -35 divide both sides by -5

By dividing, you should get

X = 7 which is your answer

First of all, you have to open the paranthesis, in order to know the unknown terms and the free terms. After that, we'll keep the unknown terms on the left side of the equality and we'll move the free terms on the right side, so the relation will become:

2x-7x+35=0

-5x+35=0

-5x=-35

We'll multiply the relation above with (-1), and after that we'll divide it with (5).

(-1)*(-5)*x=(-1)*(-35)

5*x=35

(5/5)*x=35/5

**x=7**

To solve 2x-7(x-5)=0

This is an equation in one variable x with degree one(and so it is a linear equation). The principle of solving this type of equation is by collecting all the unknowns or vaiables, or x's here, on the left and all the knowns or the numbers on the right side of the equation, by simle operations. The simple operations are adding equals, removing equals, multiplying or dividing by equals (but not dividing zero- mind it!) on both sides which does not imbalance the equation.

On the left side there are two terms, 2x, connected by a minus connector to 7(x-5). Since, -7 is distributive over the two terms inside the brackets by multiplication operation, you can write -7(x-5) like -7*x -7*(-5) = -7x+35 and replace the term -7(x-5) in the expression 2x-7(x-5). This enables us to rewrite the left of the equation as below:

2x-7x+35=0.

2x and -7x are like terms and so 2x-7x is -5x.Therefore,

-5x+35=0

Subtract 35 from both sides of the equation.

-5x+35-35=0-35

Simplify.

-5x=-35.

Divide both sides by -5:

-5x/5=-35/(-5) and simplify to get the solution

x=7